Efficiency of the Palm Sugar Marketing Channel (A Case Study In Margamulya Village Garut) - Asep Permadi Gumelar; Wahid Erawan; Agus Hoerul Yusup (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
The plantation subsector is one of the agricultural industries that contributes significantly to the national economy. Since practically every component of sugar palm plants may provide income, they have a vast economic potential. Palm sugar marketing in Margamulya Village has a central problem: the large number of marketing channels, which results in low incomes for palm sugar craftsmen. This research aims to determine marketing channels and the marketing efficiency of palm sugar in Margamulya Village, Cisompet District. This research uses a survey method and method with data collection techniques of observation, interviews, questionnaires, and documentation. Data analysis uses quantitative description by analyzing marketing channels, marketing margins, farmer's share, and marketing efficiency. The research results show five marketing channel patterns in Margamulya Village. The lowest marketing margins are in channels I and II, with a total margin of Rp. 3000. Channel I involves one marketing institution, collectors, while channel II involves retailers. The highest farmer's share is in marketing channel II, with a percentage of 83%. The most efficient marketing channel is channel II, which has an efficiency value of 1.7%. Marketing efficiency analysis shows that the five marketing channels in this research are considered efficient. This research also reveals that all marketing channels have a farmer's share value, which is at the efficient criteria with a farmer's share value of >50%, causing lower costs and more efficiency in the marketing channel.